Análise da interação entre determinantes da limitação ao fluxo expiratório em homens saudáveis - Santos, Patrícia Rehder dos (2015)
Background and objective: Dysanapsis ratio (DR), peak oxygen uptake (VO₂ peak) and age are studied as determinants of expiratory flow limitation (EFL) during exercise. However, it is not yet known whether they can elucidate EFL in young and middle-aged healthy individuals of the same sex. The objective of this study was to investigate the interaction between determinants of LFE (VO₂ peak, DR and age) during different exercise intensities performed in cycle ergometer. Methods: Twenty Two men, 11 young men, and 11 middle-aged men performed the following tests: measurement of respiratory muscle strength, lung function test (DR), cardiopulmonary test (VO₂ peak), and two constant load tests to assess EFL at loads of 75% and 125% of gas exchange threshold (GET). The unpaired t test and the Mann-Whitney test were used to compare groups and two-way ANOVA was used to analyze the effect of age and exercise intensity on the variables of the constant load test (CLT). Stepwise multiple regression was used to analyze the interaction between VO₂ peak, DR, and age and EFL. The significance level was set at p<0.05. Results: Only the middle-aged group presented EFL at both exercise intensities; the groups were similar in relation to respiratory muscle strength, VO₂ peak, and DR; EFL was not associated with VO₂ peak or DR, but it was associated with age during high-intensity exercise (p<0.001). Conclusion: In the experimental conditions, age was the only factor that was related to the presence of EFL during exercise.